Evaluating the effect of multi-touch behaviours on Android unlock patterns. (11th July 2016) - Meng, Weizhi
Abstract : Purpose: This paper aims to evaluate the effect of multi-touch behaviours on creating Android unlock patterns (AUPs) by realising that users can perform more actions in touch-enabled mobile phones. Design/methodology/approach: The author conducted two user studies with a total of 45 participates and performed two major experiments in the main user study. Findings: The user study indicates that the multi-touch behaviours can have a positive impact on creating patterns; however, there are only nine touchable points for the original AUPs, which may reduce the usability when performing a multi-touch movement. Research limitations/implications: An even larger user study could be conducted to further analyse the patterns generated by users, that is, to analyse the specific password space by integrating the behaviours of multi-touch and to involve more types of multi-touch behaviours in creating an AUP. Practical implications: This work explores the effect of multi-touch movement on creating AUPs. The results should be of interest for software developers and security researchers for exploring the effect of multi-touch behaviours on the creation of graphical passwords on mobile phones. Originality/value: The author conducts two user studies with a total of 45 participants to investigate the impact of multi-touch behaviours on creating AUPs. In addition, to address the issue of usability, the author proposes two ways: increasing the number of touchable points and improve the rules of pattern creation.